IMPLEMENTASI SISTEM PEMESANAN TIKET BUS ONLINE PADA PO HARYANTO MENGGUNAKAN METODE ZACHMAN FRAMEWORK - Sugiyono Sugiyono; Sus Kristiyaningsih (CKI ON SPOT, 2021)
The development of information technology has developed rapidly and affects almost all aspects of life, one of the information media is the internet. The internet is a medium of information that is very easy to access through various communication media, computers, mobile phones and smartphones. The number of media to access the internet is in line with the number of internet users. PO. Haryanto is a company engaged in the field of bus transportation services in which the presentation of ticket reservations, departure schedule information, and payment transactions is still manual which is one of the problems. In order to facilitate prospective passengers to get these services, it is necessary to have an online WEB-based bus ticket booking application. In this study, to build the application using object-oriented design methods using UML (Unfied Modeling Language). The application consists of two parts namely, Admin and users (users). This bus booking system was created using the Zachman Framework method with the PHP Programming Language with Framework, CodeIgniter and PHP Myadmin as a database server. Test results using Black-Box testing and Beta Testing show that the system can function according to user needs. In addition, based on the results of tests that have been done, the application is declared to be running well in accordance with the testing criteria.